2008
DOI: 10.1007/s00421-008-0947-8
|View full text |Cite
|
Sign up to set email alerts
|

Is the balance between skeletal muscular metabolic capacity and oxygen supply capacity the same in endurance trained and untrained subjects?

Abstract: We attempted to test whether the balance between muscular metabolic capacity and oxygen supply capacity in endurance-trained athletes (ET) differs from that in a control group of normal physically active subjects by using exercises with different muscle masses. Methods:We compared maximal exercise in 9 ET subjects (Maximal oxygen uptake [VO 2 max] 64 ml·kg -1 ·min -1  SD 4) and 8 controls (VO 2 max 464 ml·kg -1 ·min -1 ) during one-legged knee extensions (1-KE), two-legged knee extensions (2-KE) and bicyclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This increase in blood flow is a consequence of an increase in local vascular conductance, albeit muscle blood flow is balanced by sympathetic vasoconstrictor activity during whole-body exercise (Secher et al 1977, Volianitis & Secher 2002, Mortensen et al 2005, Rud & Hallen 2009. Both muscle oxidative capacity and one-legged VO 2 max were increased by one-legged endurance training in endurance-trained subjects, without affecting their VO 2 max for cycling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This increase in blood flow is a consequence of an increase in local vascular conductance, albeit muscle blood flow is balanced by sympathetic vasoconstrictor activity during whole-body exercise (Secher et al 1977, Volianitis & Secher 2002, Mortensen et al 2005, Rud & Hallen 2009. Both muscle oxidative capacity and one-legged VO 2 max were increased by one-legged endurance training in endurance-trained subjects, without affecting their VO 2 max for cycling.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, training-induced increase in muscular oxidative capacity affects both oxygen delivery and extraction and During exercise, muscle perfusion increases with intensity to suffice the oxygen demand. This increase in blood flow is a consequence of an increase in local vascular conductance, albeit muscle blood flow is balanced by sympathetic vasoconstrictor activity during whole-body exercise (Secher et al 1977, Volianitis & Secher 2002, Mortensen et al 2005, Rud & Hallen 2009. Accordingly, at high exercise intensities, when a maximal cardiac output is approached, the increase in blood flow to the exercising muscles is restricted and the increase in oxygen uptake per unit of developed power attenuated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies indicate that the oxygen consumption of the working muscles (i.e., quadriceps femoris) at maximal exercise for the single-leg knee-extensor ergometer are approximately two to three times higher than the oxygen consumption for the same muscles during cycle ergometry [ 33 , 34 , 35 ]. For example, Ru and Hallén [ 36 ] reported that mass-specific oxygen uptake (i.e., dividing the net oxygen uptake by the active muscle mass during exercise) was significantly higher for single-leg knee-extensor ergometer versus cycle ergometry (~0.400 vs. ~0.015 L of oxygen per kg of muscle mass per min). In addition, studies have compared the EMG amplitude for the quadriceps femoris muscles, using incremental testing, between the two exercise modalities (single-leg cycle ergometry and single-leg knee-extensor ergometer) and found that the EMG amplitude is ~40% higher at maximal exercise for single-leg knee-extensor ergometer versus single-leg cycle ergometry [ 37 ].…”
Section: Discussionmentioning
confidence: 99%